Professor Lidenbrock as a Reflection of Empiricism in Jules Verne’s Journey to the Centre of the Earth - Edo Tri Fitriyanto (English Letters Department, Faculty of Letters, Universitas Sanata Dharma, 2026)
Jules Verne’s Journey to the Centre of the Earth (1864), one of the author's notable novels, is claimed for its philosophical issues. This close critical analysis attempts to examine the concept of empiricism integrated in the literary text within the moral and philosophical approaches. It focuses on the identification of Professor Lidenbrock’s character depictions and the examination of Professor Lidenbrock from the concept of empiricism. This study is a library research design, applying Murphy’s theory of characterisation in fiction and Locke’s conception of empiricism. The results show that Professor Lidenbrock is generally depicted as a curious, analytic, observant, and explorative figure, which illustrates basic empirical progressions in scientific discoveries. In line with Professor Lidenbrock’s depictions, this character reflects the idea of empiricism, which believes that sensory experience is the main source of human knowledge. This philosophical idea is illustrated in his quest for knowledge, which is grounded in direct interaction with the external world through the sensory experience. Professor Lidenbrock depicts the quest for knowledge as an intellectual activity that serves as a justification for the truth. It highlights the fundamental narrative of the character’s morality, revealing how intellectual virtue establishes the essence of humans in understanding the scientific reality of the universe.